In vitro fermentation and acidification potential of several carbohydrates sources used in concentrate-based diets for growing ruminants - Amanzougarene Z.; Yuste S.; De Vega A.; Fondevila M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This in vitro work aims to study how the different carbohydrate sources fed during the fattening of young ruminants can modulate the characteristics of ruminal fermentation. Six carbohydrate feeds (barley, B; maize, M; sorghum, S; sugarbeet pulp, BP; citrus pulp, CP; and wheat bran, WB) were tested in an in vitro semi-continuous culture system under a poorly buffered medium from 0 to 6h, and allowed pH to rise to around 6.5 from 8 to 24h. Rumen fluid was obtained from three lambs fed ad libitum on a diet composed of concentrate and barley straw. The pH from 2 to 12h was reduced at a higher extent with CP, which recorded its minimum value at 6h (5.60; P<0.05), but recovered thereafter to 6.63 at 24h. During the whole incubation period, the volume of gas recorded with CP was the highest (P<0.05), followed by B and WB, whereas the lowest volume was recorded by S. Gas production results were supported by dry matter disappearance (DMd) at 24h. Concentration of volatile fatty acids (VFA) and lactic acid was the highest with CP (P<0.05), followed by WB and B. A higher acetate proportion was observed with BP and CP (P<0.05) that recorded the lowest butyrate proportion. Regarding microbial diversity, after 8h, within each incubation series substrates clustered together, except for CP and WB. CP acidified the incubation medium in a higher extent, followed by WB and B. The capacity of substrate acidification plays an important role on dynamics of in vitro microbial fermentation.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)